2020
DOI: 10.1001/jamaneurol.2020.0682
|View full text |Cite
|
Sign up to set email alerts
|

Family History of Cluster Headache

Abstract: IMPORTANCE Genetic and environmental factors are thought to contribute to cluster headache, and cluster headache can affect multiple members of a family. A thorough understanding of its inheritance is critical to understanding the pathogenesis of this debilitating disease.OBJECTIVE To systematically review family history rates and inheritance patterns of cluster headache.EVIDENCE REVIEW A systematic review was performed in PubMed, Embase, and Cochrane Library. Search criteria were created by a librarian. Artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 102 publications
1
28
0
Order By: Relevance
“…Third, CH is an inherited disorder and has multiple hereditary patterns; the most common pattern being autosomal dominant, followed by autosomal recessive ( 23 ). Studies in the Western population show a higher positive family history of CH (5–17%) ( 1 , 3 , 6 , 8 ) compared to that of studies in Asian populations (0–6.7%) ( 12 , 15 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Third, CH is an inherited disorder and has multiple hereditary patterns; the most common pattern being autosomal dominant, followed by autosomal recessive ( 23 ). Studies in the Western population show a higher positive family history of CH (5–17%) ( 1 , 3 , 6 , 8 ) compared to that of studies in Asian populations (0–6.7%) ( 12 , 15 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there have been no reported familial cases of short‐lasting unilateral neuralgiform headache with autonomic symptoms (SUNA). Very little is known about the detailed genetic mechanisms behind familial TACs, although familial cluster headache is thought to involve multiple modes of inheritance 16 . Like other TACs, the apparent rarity of familial HC could be attributed to its low prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…36 Three possible culprit genes, which pertain to the topic of this review, have been identified. 35,37,38 First, a genetic polymorphism of the CLOCK (Circadian Locomotor Output Cycles Kaput) was recently found to be associated with CH. This signal strengthened after stratifying according to diurnal rhythmicity.…”
Section: Dovepressmentioning
confidence: 99%